Two concerts given by Koubitzky, Paris, March 17 and 14, 1925 - Salle Gaveau (Paris, France)::::::::::::::: (Office Mondial de Concerts; France; Paris, 2020)
Programs for the concerts at the Maison Gaveau in Paris, March 7 and 14, 1925, by Alexandre Koubitzsky, singer, and Gabriel Minet, piano. The second concert featured three of Beethoven's Gellert Lieder, op. 48.